2011
DOI: 10.1159/000329050
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Node Dysfunction Unmasked during Dobutamine Stress Echocardiography

Abstract: Sinus bradycardia and associated isorhythmic AV dissociation may be seen during dobutamine stress echocardiography. This phenomenon is usually considered a benign peri-procedural event and is thought to be secondary to the Bezold-Jarisch reflex, with profound heart rate decrease secondary to a marked increased in vagal efferent discharge. To the best of our knowledge, dobutamine stress echocardiography unmasking clinically relevant sinus node dysfunction has never been reported. We report a case of a 50-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Again, the coronary angiography revealed normal coronary anatomy, while invasive electrophysiological study revealed marked sinus node dysfunction with indication for a permanent pacemaker implantation. 9 Finally, in two other cases, reports of women aged 48 11 and 60 years, 12 experiencing severe DSE-induced PSD, the coronary angiography was normal.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Again, the coronary angiography revealed normal coronary anatomy, while invasive electrophysiological study revealed marked sinus node dysfunction with indication for a permanent pacemaker implantation. 9 Finally, in two other cases, reports of women aged 48 11 and 60 years, 12 experiencing severe DSE-induced PSD, the coronary angiography was normal.…”
Section: Discussionmentioning
confidence: 92%
“…Other published case reports did not describe an association between DSE-induced PSD and CAD either. 6 , 9 , 11 , 12 It is plausible that the higher proportion of CAD among PSD cases in the Attenhofer et al . study 4 reflects a higher level of baseline risk (i.e.…”
Section: Discussionmentioning
confidence: 96%